Atypical Divergence of SARS-CoV-2 Orf8 from Orf7a within the Coronavirus Lineage Suggests Potential Stealthy Viral Strategies in Immune Evasion - Russell Y. Neches (American Society for Microbiology, 2021)
Orf8 is one of the most puzzling genes in the SARS lineage of coronaviruses, including SARS-CoV-2. Using sophisticated sequence comparisons, we confirm its origins from Orf7a, another gene in the lineage that appears as more conserved, compared to Orf8.